What do we know about campaign finance and gender so far? The scoping review as an analysis tool with a feminist approach - Eduardo, Maria Cecília; Souza, Juliana I. Luiz; Horochovski, Rodrigo Rossi (Cuestiones de Género: de la igualdad y la diferencia, 2023)
This paper aims to present the scoping review as an analysis tool for the feminist debate. Through the use of this bibliometric technique, we surveyed the academic production of two central themes of political science: campaign finance and female political participation. To understand what has the literature shown us so far, we produced a state of the art based on 51 articles found in two databases (Scopus and Web of Science). We could see that even with the increase in production on these themes, the male authorship status quo remains, and gender-related issues in political processes continue to be peripheral in the debate. This fact reinforces the need for a feminist perspective that looks at gender beyond an analysis variable.